2023
DOI: 10.1002/ptr.7836
|View full text |Cite
|
Sign up to set email alerts
|

Prevention effect of total ginsenosides and ginseng extract from Panax ginseng on cyclophosphamide‐induced immunosuppression in mice

Abstract: Oral decoction is widely applied in traditional Chinese medicines. The polysaccharides of decoction promote the exposure of small molecules and increase their bioavailability. This study mainly compared the component and activities of total ginsenosides (TGS) and ginseng extract (GE) on immunosuppressed mice induced by cyclophosphamide. Thirty‐two mice were randomly divided into control, model, TGS, and GE groups. The mice were orally administered for 28 days and then injected with cyclophosphamide on the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…CTX is widely used in treating various cancer and allergic diseases; however, it can damage the immune system, induce disruption of the gut microbiota, and increase the risk of immunodeficiency and intestinal injury diseases, which ultimately can cause adverse effects on the immune system; therefore, CTX is also used in the establishment of immunosuppressed models. 29–31 As important immune organs, the spleen and thymus play crucial roles in regulating immune function. Consistent with the investigations of other researchers, 32–34 our current research indicated that CTX could decrease the body weight, spleen weight, and thymus weight in BALB/c mice, which indicated that CTX could cause damage to the immune system in the mice; however, the supplementation of BC encapsulated by liposomes improved these adverse alterations and exhibited a better effect than BC alone (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTX is widely used in treating various cancer and allergic diseases; however, it can damage the immune system, induce disruption of the gut microbiota, and increase the risk of immunodeficiency and intestinal injury diseases, which ultimately can cause adverse effects on the immune system; therefore, CTX is also used in the establishment of immunosuppressed models. 29–31 As important immune organs, the spleen and thymus play crucial roles in regulating immune function. Consistent with the investigations of other researchers, 32–34 our current research indicated that CTX could decrease the body weight, spleen weight, and thymus weight in BALB/c mice, which indicated that CTX could cause damage to the immune system in the mice; however, the supplementation of BC encapsulated by liposomes improved these adverse alterations and exhibited a better effect than BC alone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…, IL-5, and IL-10), which are involved in the humoral immune process. 29,35 Under healthy circumstances, these cytokines interact with each other during the immune response to maintain the dynamic balance in the human body. 36,37 Previously, researchers have reported that the supplementation of BC could rehabilitate the cytokines levels in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Th1 and Th2 serve essential roles in the coordination and intercellular communication of lymphoid, inflammatory and hematopoietic cells in the immune system ( 81 ). CP inhibits the expression of TNF-α, IFN-γ, IL-4 and IL-10, and decreases the Th1/Th2 cytokine secretion ratio ( 17 , 82 ). Both APH and CP decrease the levels of TNF-α and IL-6( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…HSCs can produce a new blood cell count to resist the reduction caused by blood deficiency. Hematopoietic cytokines, such as thrombopoietin (TPO), erythropoietin (EPO) and granulocyte-macrophage colony-stimulating factor (GM-CSF), perform vital roles in the progress of hemopoiesis ( 17 ). Cytokines are crucial in the inflammatory response to anemia and are necessary for re-establishing flow to the afflicted organs ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has investigated natural compounds such as curcumin, ginseng, and flavonoids for their ability to modulate immune responses [25][26][27]. Ginseng and its bioactive components have demonstrated immune-stimulating properties in animal models of immunosuppression induced using CTX, including increased activity of NK cells and enhanced antibody production [9,28,29]. Our study designated red ginseng extract (100 mg/day) as the positive-control.…”
Section: Discussionmentioning
confidence: 99%